Virtual currencies and their potential impact on financial markets and monetary policy - Marek Dabrowski; Lukasz Janikowski (Center for Social and Economic Research (CASE), 2018)
Virtual currencies are a contemporary form of private money. Thanks to their technological properties, their global transaction networks are relatively safe, transparent, and fast. This gives them good prospects for further development. However, they remain unlikely to challenge the dominant position of sovereign currencies and central banks, especially those in major currency areas. As with other innovations, virtual currencies pose a challenge to financial regulators, in particular because of their anonymity and trans-border character.
Keywords: E42; E58; F31; G18; G28; N21; N23; 330; virtual currency; private money; sovereign currency; free banking; monetary policy; central bank; financial regulation; financial market; currency substitution